PREDICTORS OF DISEASE SEVERITY IN COVID-19 PATIENTS - Djurić, Milivoje; Makević Djurić, Mirjana; Kavećan, Ivana; Vujčić, Isidora; Maksimović, Nataša; Maksimović, Katarina; Georgievski-Brkić, Biljana; Maksimović, Jadranka (HEALTH CARE, 2025)
Background/aim: In the clinical picture of COVID-19 respiratory symptomatology dominates, but it is basically a multisystemic disorder. The aim of this study was to identify predictors of severe forms of COVID-19 defined as the need for assisted ventilation (non-invasive or invasive mechanical ventilation). Methods: The research was conducted as a retrospective cohort study at the General hospital "Laza K. Lazarević” in Šabac for the period from1.4.2020. to 14.11.2020. The relationship between demographic and clinical parameters of patients and the need for assisted ventilation was examined by logistic regression analysis. Results: The study included 516 patients, 334 male subjects (64.7%), with the age of 60 and over (52.7%). The most commonly reported symptoms were fever (89%) and generalized weakness (68.8%). Mechanical ventilation was required by 44 patients, majority of whom were male (64.7%). The dominant comorbidities in mechanically ventilated group were hypertension (63.6%) and diabetes (22.7%). According to multivariate analysis independent risk factors for assisted ventilation were: fever (p=0.016), duration of illness more than seven days before hospitalization (p=0.023), oxygen saturation (sO2) <90% (p=0.002), arrhythmia(p=0.001), leukocytosis(p=0.034), and CRP≥50 mg/l (p=0.002). Conclusion: The risk of assisted ventilation was higher in patients with fever, sO2<90% on admission to hospital, duration of illness more than seven days before hospitalization, arrhythmia, leukocytosis, lymphopenia<1.0x109 and CRP>50 mg/l.